Next-generation sequencing of a combinatorial peptide phage library screened against ubiquitin identifies peptide aptamers that can inhibit the in vitro ubiquitin transfer cascade - Lisowska, Małgorzata; Lickiss, Fiona; Gil-Mir, Maria; Huart, Anne-Sophie; Trybala, Zuzanna; Way, Luke; Hernychova, Lenka; Krejci, Adam; Muller, Petr; Krejcir, Radovan; Zhukow, Igor; Jurczak, Przemyslaw; et al. (Frontiers in Microbiology, 2022)
Defining dynamic protein-protein interactions in the ubiquitin conjugation reaction is a challenging research area. Generating peptide aptamers that target components such as ubiquitin itself, E1, E2, or E3 could provide tools to dissect novel features of the enzymatic cascade. Next generation deep sequencing platforms were used to identify peptide sequences isolated from phage-peptide libraries screened against Ubiquitin and its orthologue NEDD8. In over three rounds of selection under differing wash criteria, over 13,000 peptides were acquired targeting ubiquitin whilst over 10,000 peptides were selected against NEDD8. The overlap in peptides against these two proteins was less than 5% suggesting a high degree in specificity of Ubiquitin or NEDD8 towards linear peptide motifs. Two of these ubiquitin binding-peptides were identified that inhibit both E3 ubiquitin ligases MDM2 and CHIP. NMR analysis highlighted distinct modes of binding of the two different peptide aptamers. These data highlight the utility of using next generation sequencing of combinatorial phage-peptide libraries to isolate peptide aptamers towards a protein target that can be used as a chemical tool in a complex multi-enzyme reaction.